THE INFLUENCE OF PERCEPTIONS OF TEACHER WELFARE AND TEACHING EXPERIENCE ON CAREER READINESS TO BECOME A TEACHER IN EDUCATION STUDENTS OF THE FACULTY OF ECONOMICS, STATE UNIVERSITY OF JAKARTA THROUGH SELFEFFICACY AS A MEDIATION VARIABLE - Hasanah, Uswatun; Febriantina, Susan; Rachmadania, Rizki Firdausi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the influence of learning culture, student personality characteristics, readiness to learn boldly on learning satisfaction. The research was conducted for 10 (ten) months starting from December 2020 to October 2021. The research method was quantitative with the type of research that was explanatory. The sample used in this study found 131 respondents from the education students of the Faculty of Economics, State University of Jakarta. The data collection technique used a proportional random technique. The data analysis technique used SmartPLS software version 3.0 PLS (Partial Least Square) with structural equation analysis (SEM). The results showed that each variable had a significant effect.